Community-oriented network measurement infrastructure (CONMI) workshop report. - claffy, kc
This report summarizes issues discussed at the first CONMI workshop held on 30 March 2005 in Boston, Massachusetts. Sponsored by the National Science Foundation's Office of Cyberinfrastructure (OCI-0532233), the workshop was intended to begin a discussion regarding the viability and utility of a community-oriented network measurement infrastructure. This report was published 20 December 2005 online at: http://www.caida.org/workshops/conmi/.
Keywords: Computer systems organization; Performance of systems; Measurement techniques; Computer communication networks; Network operations; Network monitoring; Information systems; Information storage and retrieval; Online information services; Data sharing; Experimentation; Measurement